Functional assessment of patients before and 6 months after total knee replacement - Majewska, Joanna; Szczepanik, Magdalena; Jabłoński, Jarosław; Snela, Sławomir; Jarmuziewicz, Agnieszka; Bazarnik-Mucha, Katarzyna; Szymczyk, Daniel (European Journal of Clinical and Experimental Medicine, 2016)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Endoprosthetics is currently most common method of the treatment of advanced osteoarthritis, including knee joint osteoarthritis. Its main goal is to restore patients functional independence in activities of daily living through reducing pain and disability. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Objective. The aim of this study was functional assessment of the patients after total knee replacement (TKR) considering subjects age and gender, BMI and mean duration of the disease. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. 70 patients (59 females and 11 males), qualified for total knee replacement surgery due to the primary knee osteoarthritis (KO), participated in this study. Mean age of the patients in the study group was 66,5 years. Visual Analogue Scale (VAS), Knee Injury and Osteoarthritis Outcome Score (KOOS), Global Rating Scale, Up&Go Test, Five Time Sit to Stand Test and 10-meters walking test were used for the functional assessment of the patients. Additionally, the measurement of the range of motion of the operated and non-operated knee joint were performed. The study was performed twice; the first study was conducted one week before the surgery and the second study-six months after. For the purpose of the presentation of the results of this study mean value, median, standard deviation and Spearman’s rank correlation coefficient were used. Non-parametric Wilcoxon and Mann-Whitney test were used for the statistical analysis. The level of statistical significance was assumed at α < 0.05. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Within six months after total knee replacement surgery (TKR) statistically significant improvement of the results of all functional tests and scales used in this study were observed.